The efficacy and safety of Niaoduqing granules in the treatment of diabetic kidney disease: a systematic review and meta-analysis - Song, Chaoqun; Zhu, Zhiyue; Liu, Le; Liu, Shilin; Li, Yuandong; Xiao, Yang; Wu, Chunwei; Nan, Zheng (Frontiers in Pharmacology, 2023)
Background: Diabetic nephropathy (DN) is the main cause of chronic kidney disease (CKD) and end-stage renal failure (ESRF), and the control of disease progression and adverse events during treatment needs to be improved. Objective: This study aimed to systematically evaluate the clinical efficacy and safety of Niaoduqing Granules (NDQG) in the treatment of diabetic kidney disease (DKD). Method: Randomized controlled trial (RCT) of NDQG for DKD were included in Chinese and English databases from the establishment to 31 August 2022. The quality of the literature was assessed using the risk of bias tool of the Cochrane Handbook. At 95% confidence interval (CI), relative risk (RR) and Cohen's d were used for the categorical and continuous variables, respectively, and Stata 16.0 software was used for statistical analysis. Funnel plot and Egger tests were used to assess publication bias. Result: A total of 4006 patients were included in 52 Randomised controlled trials (RCTs), including 1987 cases in the control group and 2019 cases in the treatment group. Compared with conventional treatment (CT), combined NDQG therapy is more effective in improving clinically effective, kidney function (UAER, 24hUTP, BUN , SCr , CCr, Cys-C), level of glucose metabolism (FBG, HbA1c), level of lipid metabolism (TC,TG ), inflammatory factors (Hs-CRP , IL-18 and TNF-α ), indicators of oxidative stress (MDA and AOPP). In terms of improving UA , 2hPG, HDL-C , Hb), and SOD , the effect is not obvious. Adjuvant treatment with NDQG did not increase the incidence of adverse reactions in the control group . Obvious publication bias was detected by Funnel plot and Egger’s test. Conclusion: Our meta-analysis showed that adjuvant treatment with NDQG has more advantages than CT alone in the DKD treatment, which could improve clinical efficiency, kidney function, level of glucose metabolism , level of lipid metabolism, inflammatory factors, oxidative stress indicators, at the same time, NDQG are also relatively safe. However, more high-quality studies are needed to provide more reliable evidence for clinical use.